2017
DOI: 10.1039/c6tc05139a
|View full text |Cite
|
Sign up to set email alerts
|

Modular synthesis of asymmetric rylene derivatives

Abstract: Modular synthesis of asymmetric rylenes from commercially available naphthalic anhydride derivatives provides access to novel materials with tunable functional handles at the imide-position, site-specific incorporation of bay position substituents and tailored extension of the molecular core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…As depicted in Scheme 1, the key precursor 2 was obtained in 85 % yield via Stille coupling reaction of the starting materials 1 [12] and (E)‐1,2‐bis(tributyltin)ethylene. Subsequently, 2 underwent a photocyclization reaction with a catalytic amount of iodine afforded the PiDI in 94 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…As depicted in Scheme 1, the key precursor 2 was obtained in 85 % yield via Stille coupling reaction of the starting materials 1 [12] and (E)‐1,2‐bis(tributyltin)ethylene. Subsequently, 2 underwent a photocyclization reaction with a catalytic amount of iodine afforded the PiDI in 94 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…Although nature synthesizes asymmetric biomolecules with marvelous efficiencies 41 , it is a challenge for synthetic chemists to prepare asymmetric compounds due to poor selectivity and low yields 42 . In the case of n-type OSCs, several studies on the synthesis of asymmetric PDI have been reported [43][44][45] .…”
Section: Synthesismentioning
confidence: 99%
“…To address these limitations, PBI cores were modified with various substituents on their imide nitrogen atoms (N-substitution, X ) or on bay-region positions (bay-modifications, Y ), or by cracking the C–C bond of the PBI backbone to create bisnaphthalimide (BNI) derivatives (Scheme 1). 13–20…”
Section: Introductionmentioning
confidence: 99%
“…To address these limitations, PBI cores were modified with various substituents on their imide nitrogen atoms (N-substitution, X) or on bay-region positions (bay-modifications, Y), or by cracking the C-C bond of the PBI backbone to create bisnaphthalimide (BNI) derivatives (Scheme 1). [13][14][15][16][17][18][19][20] PBIs substituted with dendrons at the bay and/or imide positions can self-organize into 2D and 3D columnar periodic arrays [21][22][23][24][25][26][27][28] exhibiting high charge carrier mobility of interest for photovoltaic and other electronic applications. For example, novel classes of complex helical columns assembled from (3,4,5)nG1-m-PBI substituted with dendrons containing 0-4 methylenic units (m) between the imide group of the dendrons and 6-12 methylenic units (n) in their alkyl groups were reported by Percec et al (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%